CLINICAL TESTS OF PHYTOPREPARATE IN COMPLEX THERAPY OF ACUTE RESPIRATORY DISEASES - Вековцев, Андрей Алексеевич; Позднякова, Ольга Георгиевна; Белавина, Галина Андреевна; Позняковский, Валерий Михайлович (Medicine in Kuzbass, 2019)
The aim of the study – the clinical approbation of a new phytocomplex in the complex therapy of acute respiratory diseases.Materials and methods. Thirty patients with acute respiratory diseases were examined, whose diet, during 28 days, included a specialized product in the form of a phytocomplex of 1 capsule 2 times a day. Clinical trials were carried out on the basis of the city hospital N 3 (Tomsk).Results. The parameters of changes in clinical symptoms of the disease, hematological tests, subpopulation composition of peripheral blood lymphocytes, serum IFN-γ content indicate activation of the antiviral response of immunocompetent cells, reduction of the inflammatory process, acceleration of the processes of relief of the general intoxication syndrome, which as a whole makes it possible to shorten the duration of the disease.The conclusion. Clinical evidence of the effectiveness of the tested form of biologically active additive with the presence of anti-inflammatory and immunomodulating effect was obtained. Phytopreparation can be recommended in the complex therapy of acute respiratory diseases and the prevention of their occurrence.
Keywords: phytopreparation; acute respiratory diseases; complex therapy; prevention; efficiency